The Use Of Talking Stick Method On The Theme Of Animal And Human Movement Organs In Grade 5 To Improve Student's Speaking Skills - Afandi Nur Rozianzah; Bambang Edi Siswanto (IJPSE : Indonesian Journal of Primary Science Education, 2022)
ABSTRACT This research aims to improve skills speak through the use of a method of talking stick class students V SD Islam Al-Washoya Kurto Rejo Ngoro Jombang. Skill talk observed in this research include linguistic nonlinguistic. aspects and on the aspect of pronunciation, linguistic consisting of intonation and, choice of words while on the aspect of nonlinguistic consisting of the smooth, loudness voice and mastery of the topic. This kind of research is to research a class action ( PTK ). The subject of this research is the student Class v SD Islam Al-Washoya Kurto Rejo Ngoro Jombang 15. interviewed students A design study that used is a model Kemmis and MC. Which includes the planning stage, Taggart the implementation of the act of, , observation and the reflections. An instrument of data used is the test to show off, work sheets of observation teachers and students as well as. Documentation Data collection analysis techniques used are descriptive. Quantitative data analysis. The research indicated that the use of the media talking stick can increase speaking skills students primary school class V Islam Al-Washoya Kurto Rejo Ngoro Jombang in terms of the process and the results of. An increase in the process in terms of rata-rata observations the activity of students who were not even in good category in the cycle I with the percentage 86,66 % increase in the cycle will be 93,33 % and included in the category of very good. Be seen in terms of the results of, evidenced by the value of average talk students skills on initial conditions 63,38 increased to 74,88 on cycle I and increased to 78,44 on II. The percentage KKM also increased from 60 % in pre the act of increased to 80 % in the I and 90 % in II cycle. Keywords : Skill speak , a method of talking stick